Modern Monetary Theory and the public purpose - Dirk H. Ehnts; Maurice Höfgen (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2020)
This paper investigates how the concept of public purpose is used in Modern Monetary Theory (MMT). As a common denominator among political scientists, the idea of public purpose is that economic actions should aim at benefiting the majority of the society. However, the concept is to be considered as an ideal of a vague nature, which is highly dependent on societal context and, hence, subject to change over time. MMT stresses that government spending plans should be designed to pursue a certain socio-economic mandate and not to meet any particular financial outcome. The concept of public purpose is heavily used in this theoretical body of thought and often referred to in the context of policy proposals as the ideas of universal job guarantee and banking reform proposals show. MMT scholars use the concept as a pragmatic benchmark against which policies can be assessed. With regards to the definition of public propose, MMT scholars agree that it is dependent on the social-cultural context. Nevertheless, MMT scholars view universal access to material means of survival as universally applicable and in that sense as the lowest possible common denominator.
Keywords: 330; Modern Monetary Theory; Public Purpose; Economy for the Common Good; Fiscal Policy; Monetary Policy